Betacyanin Biosynthetic Genes and Enzymes Are Differentially Induced by (a)biotic Stress in Amaranthus hypochondriacus - Casique-Arroyo, Gabriela; Martínez-Gallardo, Norma; González de la Vara, Luis; Délano-Frier, John P. (PLOS ONE, 2014)
An analysis of key genes and enzymes of the betacyanin biosynthetic pathway in Amaranthus hypochondriacus (Ah) was performed. Complete cDNA sequence of Ah genes coding for cyclo-DOPA 5-O glucosyltransferase (AhcDOPA5-GT), two 4, 5-DOPA-extradiol-dioxygenase isoforms (AhDODA-1 and AhDODA-2, respectively), and a betanidin 5-O-glucosyltransferase (AhB5-GT), plus the partial sequence of an orthologue of the cytochrome P-450 R gene (CYP76AD1) were obtained. With the exception AhDODA-2, which had a closer phylogenetic relationship to DODA-like genes in anthocyanin-synthesizing plants, all genes analyzed closely resembled those reported in related Caryophyllales species. The measurement of basal gene expression levels, in addition to the DOPA oxidase tyrosinase (DOT) activity, in different tissues of three Ah genotypes having contrasting pigmentation levels (green to red-purple) was determined. Additional analyses were performed in Ah plants subjected to salt and drought stress and to two different insect herbivory regimes. Basal pigmentation accumulation in leaves, stems and roots of betacyanic plants correlated with higher expression levels of AhDODA-1 and AhB5-GT, whereas DOT activity levels coincided with pigment accumulation in stems and roots and with the acyanic nature of green plants, respectively, but not with pigmentation in leaves. Although the abiotic stress treatments tested produced changes in pigment levels in different tissues, pigment accumulation was the highest in leaves and stems of drought stressed betacyanic plants, respectively. However, tissue pigment accumulation in stressed Ah plants did not always correlate with betacyanin biosynthetic gene expression levels and/or DOT activity. This effect was tissue- and genotype-dependent, and further suggested that other unexamined factors were influencing pigment content in stressed Ah. The results obtained from the insect herbivory assays, particularly in acyanic plants, also support the proposal that these genes could have functions other than betacyanin biosynthesis.